2016
DOI: 10.1016/j.ypmed.2016.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Preventing large birth size in women with preexisting diabetes mellitus: The benefit of appropriate gestational weight gain

Abstract: Objective To estimate the percentage of infants with large birth size attributable to excess gestational weight gain (GWG), independent of prepregnancy body mass index, among mothers with preexisting diabetes mellitus (PDM). Study design We analyzed 2004–2008 Florida linked birth certificate and maternal hospital discharge data of live, term (37–41 weeks) singleton deliveries (N = 641,857). We calculated prevalence of large-for-gestational age (LGA) (birth weight-for-gestational age ≥ 90th percentile) and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Moreover, a large number of studies have shown that excessive GWG is a risk factor for various adverse maternal and infant outcomes in pregnant women with diabetes (28,29). Research by Kim et al (30) demonstrated that excessive weight gain during pregnancy is an independent predictor of the occurrence of fetal macrosomia, while appropriate GWG reduces the occurrence of fetal macrosomia in pregnant women with gestational diabetes by one-third. Xueqin Zhang et al (31) pointed out that excessive weight gain in the second trimester of pregnancy is a high-risk factor for large-for-gestationalage (LGA) infants, whereas excessive weight gain in the third trimester of pregnancy is a high-risk factor for preeclampsia and cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a large number of studies have shown that excessive GWG is a risk factor for various adverse maternal and infant outcomes in pregnant women with diabetes (28,29). Research by Kim et al (30) demonstrated that excessive weight gain during pregnancy is an independent predictor of the occurrence of fetal macrosomia, while appropriate GWG reduces the occurrence of fetal macrosomia in pregnant women with gestational diabetes by one-third. Xueqin Zhang et al (31) pointed out that excessive weight gain in the second trimester of pregnancy is a high-risk factor for large-for-gestationalage (LGA) infants, whereas excessive weight gain in the third trimester of pregnancy is a high-risk factor for preeclampsia and cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive GWG has been linked to high prevalence of cesarean section and gestational hypertension, large gestational age fetals, postpartum weight retention, and child obesity. [20,32,33] On the contrary, insufficient GWG is associated with small gestational age babies, [34,35] preterm delivery, NICU admission, and stunting at 5 years. [36] Moreover, the impact due to the changes in weight and body composition during pregnancy may persist into the postpartum period and whole life of the parturients.…”
Section: Discussionmentioning
confidence: 99%
“…[16] The IOM recommendation has been widely used by various racial and ethnic groups all over the world for clinical guidance and scientific research, facilitating the comparison of international data. [11,[18][19][20] However, the recommendation may be not suitable for Asian populations because they are mainly based on the Caucasian standard. Moreover, many previous studies indicate that there may be racial differences in genetic characteristics, such as maternal height, pelvic shape.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity add significantly to the risk of large for gestational age offspring in these pregnancies [ 7 ], and excess gestational weight gain is linked to risk for neonatal macrosomia independent of glycemic control in women with type 1 diabetes [ 8 ]. Thus, women with PGDM are advised to aim for pre-pregnancy BMI in the normal range, less gestational weight gain than women without diabetes, and strict glycemic control [ 5 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%